Targeting the post-irradiation tumor microenvironment in glioblastoma via inhibition of CXCL12 - Giordano, Frank Anton; Link, Barbara; Umansky, Viktor; Herskind, Carsten (Cancers, 2019)
Radiotherapy is a mainstay in glioblastoma therapy as it not only directly targets tumor cells but also depletes the tumor microvasculature. The resulting intra-tumoral hypoxia initiates a chain of events that ultimately leads to re-vascularization, immunosuppression and, ultimately, tumor-regrowth. The key component of this cascade is overexpression of the CXC-motive chemokine ligand 12 (CXCL12), formerly known as stromal-cell derived factor 1 (SDF-1). We here review the role of CXCL12 in recruitment of pro-vasculogenic and immunosuppressive cells and give an overview on future and current drugs that target this axis.